Multi-perspective analysis of a parabolic trough collector with a gradient porous structure and hybrid nanofluid: Thermal, thermodynamic, and exergoeconomic evaluation - Iman Shahdad; Mahdi Moghimi; Mahdi Navidbakhsh (Cleaner Engineering and Technology)
Research highlights that porous media significantly enhance parabolic trough collector performance by increasing surface area and minimizing thermal losses, thereby improving energy capture. Adding nanoparticles to the heat transfer fluid can further boost this improvement by increasing the heat transfer coefficient. The present study examined a porous ring with non-uniform porosity inside the receiver, which decreases radially toward the absorber tube's inner wall. A hybrid nanofluid was created by adding Al2O3 and MWCNT nanoparticles to Therminol-VP1 oil. The main objective was to investigate the influence of the novel receiver with and without the hybrid nanofluid. Additionally, an exergoeconomic analysis was conducted to assess the cost-effectiveness of incorporating the porous ring and hybrid nanofluid. Computational fluid dynamics simulations using OpenFOAM software analyzed the effects of various Reynolds numbers (104,5×104,20×104, and 50×104), inlet temperatures (400 K and 500 K), porous ring thicknesses (0.008 m, 0.016 m, and 0.024 m), and nanoparticle volume fractions (0 %, 2 %, and 4 %) on parabolic trough collector performance. Results indicated that the gradient porous ring increased the Nusselt number by more than threefold and enhanced thermal and exergy efficiencies up to 17.3 % and 18.5 %, respectively. Adding nanoparticles optimized the Nusselt number at high Reynolds numbers but only modestly improved thermal and exergy efficiencies by 1.7 % and 2.3 %. Exergoeconomic analysis revealed that the porous ring increased net profit up to 30.3 % and reduced the total cost per unit of heat load by 7.39 %, whereas the addition of nanoparticles decreased net profit by 25.5 % and increased costs by 9.2 %.